Tryptophan catabolites, inflammation, and insulin resistance as determinants of chronic fatigue syndrome and affective symptoms in long COVID - Al-Hakeim, Hussein Kadhem; Khairi Abed, Anwar; Rouf Moustafa, Shatha; Almulla, Abbas F.; Maes, Michael (Frontiers in Molecular Neuroscience, 2023)
Critical COVID-19 disease is accompanied by depletion of plasma tryptophan (TRY) and increases in indoleamine-dioxygenase (IDO)-stimulated production of neuroactive tryptophan catabolites (TRYCATs), including kynurenine (KYN). The TRYCAT pathway has not been studied extensively in association with the physiosomatic and affective symptoms of Long COVID. In the present study, we measured serum TRY, TRYCATs, insulin resistance (using the Homeostatic Model Assessment Index 2-insulin resistance, HOMA2-IR), C-reactive protein (CRP), physiosomatic, depression, and anxiety symptoms in 90 Long COVID patients, 3–10 months after remission of acute infection. We were able to construct an endophenotypic class of severe Long COVID (22% of the patients) with very low TRY and oxygen saturation (SpO2, during acute infection), increased kynurenine, KYN/TRY ratio, CRP, and very high ratings on all symptom domains. One factor could be extracted from physiosomatic symptoms (including chronic fatigue-fibromyalgia), depression, and anxiety symptoms, indicating that all domains are manifestations of the common physio-affective phenome. Three Long COVID biomarkers (CRP, KYN/TRY, and IR) explained around 40% of the variance in the physio-affective phenome. The latter and the KYN/TRY ratio were significantly predicted by peak body temperature (PBT) and lowered SpO2 during acute infection. One validated latent vector could be extracted from the three symptom domains and a composite based on CRP, KYN/TRY, and IR (Long COVID), and PBT and SpO2 (acute COVID-19). In conclusion, the physio-affective phenome of Long COVID is a manifestation of inflammatory responses during acute and Long COVID, and lowered plasma tryptophan and increased kynurenine may contribute to these effects.